Cloning of a Gene Encoding Protease from Bacillus halodurans CM1 into Escherichia coli DH5α and Expression Analyses of the Gene Product - Helianti, Is; Furgeva, Natasha; Mulyawati, Lina; Ferniah, Rejeki Siti; Kusumaningrum, Hermin Pancasakti (UI Scholars Hub, 2018)
Bacillus halodurans strain CM1 is an Indonesia alkalothermophilic bacterium isolated from Cimanggu Hot Spring, Bandung, West Java. This bacterial strain produces high levels of thermoalkalophilic xylanase. It has also been predicted to produce other potential industrial enzymes, including protease. For production and application of protease in the future, the protease gene from B. halodurans CM1 was cloned into Escherichia coli. The protease gene was isolated from B. halodurans CM1 by the PCR approach using primers designed based on the GenBank. The PCR product was then ligated into pGEM-T Easy vector, transformed into E. coli DH5α, verified, and analyzed based on DNA sequencing data using the BLAST search tool. A 1086-bp protease gene was obtained that exhibited a very high sequence similarity (99%) with that of alkaline protease gene from B. halodurans C-125. When the culture of this positive recombinant E. coli DH5α containing the protease gene was spotted onto calcium caseinate agar, a clear zone appeared after incubation at 50 °C. This result demonstrated that the protease gene was expressed in this recombinant E. coli DH5α.